Borrelia miyamotoi sensu lato Seroreactivity and Seroprevalence in the Northeastern United States - Peter J. Krause; Sukanya Narasimhan; Gary P. Wormser; Alan G. Barbour; Alexander E. Platonov; Janna Brancato; Timothy Lepore; Kenneth Dardick; Mark Mamula; Lindsay Rollend; Tanner K. Steeves; Maria Diuk-Wasser; et al. (Emerging Infectious Diseases, 2014)
Borrelia miyamotoi sensu lato, a relapsing fever Borrelia sp., is transmitted by the same ticks that transmit B. burgdorferi (the Lyme disease pathogen) and occurs in all Lyme disease–endemic areas of the United States. To determine the seroprevalence of IgG against B. miyamotoi sensu lato in the northeastern United States and assess whether serum from B. miyamotoi sensu lato–infected persons is reactive to B. burgdorferi antigens, we tested archived serum samples from area residents during 1991–2012. Of 639 samples from healthy persons, 25 were positive for B. miyamotoi sensu lato and 60 for B. burgdorferi. Samples from ≈10% of B. miyamotoi sensu lato–seropositive persons without a recent history of Lyme disease were seropositive for B. burgdorferi. Our resultsA suggest thatA human B. miyamotoiA sensu latoA infection may be common in southern New England and that B. burgdorferi antibody testing is not an effective surrogate for detecting B. miyamotoi sensu lato infection.